Consumer Price Index And Inflation On Bi-7 Day Reverse Repo Rate - Mutmainnah Mutmainnah; Mahfiyah Mahfiyah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
The research aims to show the relationship between the consumer price index (CPI) and inflation on the BI7DRR level. This research uses a quantitative descriptive approach. The data used in this research analysis is secondary data. The population in this study is all Indonesian CPI, inflation, and BI7DRR time series data. The sampling technique for this research uses purposive sampling, namely time series data on CPI, inflation, and Indonesia's BI7DRR from January 2020 to June 2023. The research results show that the CPI has an insignificant negative effect on BI7DRR. Inflation has a significant positive effect on BI7DRR. CPI and inflation have a significant effect on BI7DRR. The results of this research can be used to determine the relationship between CPI and inflation about BI7DR and to decide actions that the government can take to determine monetary policy to stabilize prices.